Rechargeable lithium battery
By introducing carbon nanotubes and specific additives into rechargeable lithium batteries, a stable solid electrolyte interface is formed, which solves the problem of electrolyte decomposition under high voltage and high temperature, improves battery stability and lifespan, and achieves improved battery performance.
Patent Information
- Application Number
- CN202211023735.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-08-26
- Filing Date
- 2022-08-23
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2042-08-23
AI Technical Summary
Existing rechargeable lithium batteries suffer from electrolyte decomposition under high voltage and high temperature conditions, leading to battery performance degradation and insufficient safety. In particular, at high temperatures, electrolyte oxidation accelerates side reactions, increases internal battery pressure and electrode resistance, and affects battery stability and cycle life.
An electrolyte consisting of a positive electrode layer, a negative electrode layer, a non-aqueous organic solvent, and lithium salt is used. Carbon nanotubes and specific additives are added to the positive electrode layer. The compounds represented by chemical formula 1 are used to suppress electrolyte decomposition and side reactions, forming a stable solid electrolyte interface, reducing gas generation, and improving battery stability and high-temperature storage characteristics.
It effectively suppresses electrolyte decomposition and side reactions, reduces gas generation, improves battery stability and cycle life, and enhances initial resistance and storage characteristics at high temperatures.
Smart Images

Figure CN115732742B_ABST
Abstract
Description
[0001] Cross-references to related applications
[0002] This application claims priority and benefit to Korean Patent Application No. 10-2021-0113345, filed with the Korean Intellectual Property Office on August 26, 2021, the entire contents of which are incorporated herein by reference. Technical Field
[0003] This disclosure relates to rechargeable lithium batteries. Background Technology
[0004] Rechargeable lithium-ion batteries can be recharged, and their high energy density per unit weight is three times or more than that of conventional lead-acid, nickel-cadmium, nickel-metal hydride, and nickel-zinc batteries. Rechargeable lithium-ion batteries can also be charged at high rates, and are therefore commercially manufactured for use in laptops, cell phones, power tools, and electric bicycles, and research is actively underway to further improve their energy density.
[0005] In particular, as IT devices increasingly achieve high performance, they require high-capacity batteries. High capacity can be achieved by expanding the voltage range and increasing energy density. However, the oxidation of the electrolyte in the high voltage range causes a problem that degrades the performance of the positive electrode.
[0006] For example, LiPF6, the lithium salt most commonly used as an electrolyte, reacts with the electrolyte solvent, leading to solvent consumption and the generation of large amounts of gas. LiPF6 decomposes and produces decomposition products such as HF and PF5, causing electrolyte consumption and resulting in performance degradation and safety issues at high temperatures.
[0007] Electrolyte decomposition products deposit as a film on the electrode surface, increasing the battery's internal resistance and ultimately leading to performance degradation and shortened cycle life. In particular, the rapid reaction at higher temperatures further accelerates this side reaction, and the gaseous components produced by the side reaction can quickly increase the battery's internal pressure, thus having a fatally adverse effect on battery stability.
[0008] In the high voltage range, the oxidation of the electrolyte is greatly accelerated, and it is therefore known to greatly increase the resistance of the electrodes during long-term charging and discharging processes.
[0009] Therefore, an electrolyte suitable for high voltage and high temperature conditions is needed. Summary of the Invention
[0010] The embodiments provide a rechargeable lithium battery that has improved battery stability by suppressing electrolyte decomposition and side reactions with the electrodes, while having improved initial resistance and high-temperature storage characteristics by improving the impregnation of the positive electrode in the electrolyte.
[0011] Embodiments of the present invention provide a rechargeable lithium battery, comprising: a positive electrode including a positive electrode active material layer; a negative electrode including a negative electrode active material layer; and an electrolyte including a non-aqueous organic solvent, a lithium salt, and additives.
[0012] The positive electrode active material layer includes positive electrode active material and carbon nanotubes.
[0013] Based on the total weight of the positive electrode active material layer, the carbon nanotube content is greater than approximately 0.1 wt% and less than approximately 3.0 wt%, and
[0014] Additives include compounds represented by chemical formula 1.
[0015] [Chemical Formula 1]
[0016]
[0017] In chemical formula 1,
[0018] X 1 It can be fluorine, chlorine, bromine, or iodine.
[0019] R 1 To R 6 Each of the following is independently hydrogen, cyano, substituted or unsubstituted C1 to C20 alkyl, substituted or unsubstituted C1 to C20 alkoxy, substituted or unsubstituted C2 to C20 alkenyl, substituted or unsubstituted C2 to C20 alkynyl, substituted or unsubstituted C3 to C20 cycloalkyl, substituted or unsubstituted C6 to C20 aryl, or substituted or unsubstituted C2 to C20 heteroaryl.
[0020] n is an integer that is either 0 or 1.
[0021] Compounds represented by chemical formula 1 may include compounds represented by chemical formula 1A or chemical formula 1B.
[0022]
[0023] In chemical formula 1A and chemical formula 1B,
[0024] X 1 It can be fluorine-, chloro-, bromine-, or iodine-based, and
[0025] R 1 To R 6 Each is independently hydrogen, substituted or unsubstituted C1 to C10 alkyl, substituted or unsubstituted C1 to C10 alkoxy, substituted or unsubstituted C2 to C10 alkenyl, or substituted or unsubstituted C2 to C10 alkynyl.
[0026] In chemical formulas 1A and 1B, R 3 and R 4 Each can be hydrogen, and R 1 R 2 R 5 and R 6 At least one of them may be a substituted or unsubstituted C1 to C10 alkyl, a substituted or unsubstituted C1 to C10 alkoxy, a substituted or unsubstituted C2 to C10 alkenyl, or a substituted or unsubstituted C2 to C10 alkynyl.
[0027] The compound represented by chemical formula 1 may be at least one of the compounds selected from group 1.
[0028] [Group 1]
[0029]
[0030] Based on 100 parts by weight of total electrolyte, the content of the compound represented by chemical formula 1 can be greater than about 0.2 parts by weight and less than about 2.0 parts by weight.
[0031] The additive may further include at least one other additive selected from vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, vinylethylene carbonate (VEC), adiponitrile (AN), succinate (SN), 1,3,6-hexanetricyanide (HTCN), propene sulpholol (PST), propane sulphololol (PS), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), and 2-fluorobiphenyl (2-FBP).
[0032] The average length of carbon nanotubes can be greater than or equal to about 5 μm and less than about 200 μm.
[0033] The average length of carbon nanotubes can range from about 5 μm to about 100 μm.
[0034] The positive electrode active material may be at least one type of lithium composite oxide represented by chemical formula 2.
[0035] [Chemical Formula 2]
[0036] Li x M 1 1-y-z-w M 2 y M 3 z M 4 w (PO4) 1-t (O2)t
[0037] In Chemical Formula 2,
[0038] 0.5≤x<1.8, 0≤y≤1.0, 0≤z≤1.0, 0<y+z+w≤1.0, 0≤t≤1.0, 0≤w≤1.0, M 1 to M 3 are each independently any one selected from the group consisting of metals Ni, Co, Mn, Fe, Al, Sr, La, and combinations thereof, and M 4 is selected from Ti, Mg, Zr, Ca, Nb, P, F, B, and combinations thereof.
[0039] For example, the positive electrode active material may be a lithium composite oxide represented by at least one of Chemical Formula 2-1 to Chemical Formula 2-4.
[0040] [Chemical Formula 2-1]
[0041] Li x1 Ni 1-y1-z1 Co y1 M 3 z1 M 4 w1 O2
[0042] In Chemical Formula 2-1,
[0043] M 3 is Mn, Al, or a combination thereof,
[0044] M 4 is Ti, Mg, Zr, Ca, Nb, P, F, B, or a combination thereof,
[0045] 0.9≤x1<1.2, 0≤y1≤0.2, 0<z1≤0.3, 0<y1+z1≤0.5, and 0≤w1≤0.1.
[0046] [Chemical Formula 2-2]
[0047] Li x2 MnM 4 w2 O2
[0048] In Chemical Formula 2-2,
[0049] 0.9≤x2<1.2, 0≤w2≤1.0, and M 4 is selected from Ti, Mg, Zr, Ca, Nb, P, F, B, or a combination thereof.
[0050] [Chemical Formula 2-3]
[0051] Li x3CoM 4 w3 O2
[0052] In Chemical Formula 2-3,
[0053] M 4 is Ti, Mg, Zr, Ca, Nb, Fe, P, F, B, or a combination thereof,
[0054] 0.5<x3≤1, and 0≤w3≤0.1.
[0055] [Chemical Formula 2-4]
[0056] Li x4 Fe 1-z4 M 3 z4 M 4 w4 PO4
[0057] In Chemical Formula 2-4,
[0058] M 3 is Co, Ni, or a combination thereof,
[0059] M 4 is Ti, Mg, Zr, Ca, Nb, P, F, B, or a combination thereof,
[0060] 0.9≤x4≤1.8, 0≤z4≤0.3, and 0≤w4≤0.1.
[0061] A rechargeable lithium battery with improved initial resistance and high-temperature storage characteristics can be achieved by suppressing an increase in internal resistance of the battery. Description of the Drawings
[0062] Figure 1 is a schematic view illustrating a rechargeable lithium battery according to an embodiment of the present invention.
[0063] <Description of Symbols>
[0064] 100: Rechargeable lithium battery
[0065] 112: Negative electrode
[0066] 113: Separator
[0067] 114: Positive electrode
[0068] 120: Battery housing
[0069] 140: Sealing member Detailed Description of the Embodiments
[0070] The following description, with reference to the accompanying drawings, details a rechargeable lithium battery according to embodiments of the present invention. However, these embodiments are exemplary, and the invention is not limited thereto; rather, it is defined by the scope of the claims.
[0071] In the following text, unless otherwise defined, “substituted” means that the hydrogen atoms of a compound are replaced by substituents selected from the following: halogen atom (F, Br, Cl or I), hydroxyl, nitro, cyano, amino, azide, amido, hydrazine, hydrazone, carbonyl, carbamoyl, thiol, ester, carboxyl or a salt thereof, sulfonic acid or a salt thereof, phosphate or a salt thereof, C1 to C20 alkyl, C2 to C20 alkenyl, C2 to C20 alkynyl, C6 to C30 aryl, C7 to C30 aralkyl, C1 to C4 alkoxy, C1 to C20 heteroalkyl, C3 to C20 heteroaralkyl, C3 to C30 cycloalkyl, C3 to C15 cycloalkenyl, C6 to C15 cycloalkynyl, C2 to C20 heterocycloalkyl, and combinations thereof.
[0072] Based on the type of separator and electrolyte, rechargeable lithium batteries can be classified as lithium-ion batteries, lithium-ion polymer batteries, and lithium polymer batteries, and based on shape, they can be classified as cylindrical, prismatic, coin-shaped, and pouch-shaped, etc. Furthermore, based on size, they can be block-shaped or thin-film type. The structures and manufacturing methods of these batteries related to this disclosure are well known in the art.
[0073] In this document, a cylindrical rechargeable lithium battery will be described as an example of a rechargeable lithium battery. Figure 1 The schematic diagram illustrates the structure of a rechargeable lithium battery according to an embodiment. (Reference) Figure 1 According to an embodiment, a rechargeable lithium battery 100 includes: a battery cell including a positive electrode 114, a negative electrode 112 facing the positive electrode 114, a separator 113 between the positive electrode 114 and the negative electrode 112, and an electrolyte (not shown) impregnating the positive electrode 114, the negative electrode 112 and the separator 113; a battery housing 120 housing the battery cell; and a sealing member 140 sealing the battery housing 120.
[0074] The following describes a more detailed configuration of the rechargeable lithium battery 100 according to an embodiment of the present invention.
[0075] A rechargeable lithium battery according to an embodiment of the present invention includes a positive electrode, a negative electrode, and an electrolyte.
[0076] The electrolyte includes a non-aqueous organic solvent, a lithium salt, and additives, and the additives include compounds represented by chemical formula 1.
[0077] [Chemical Formula 1]
[0078]
[0079] In chemical formula 1,
[0080] X 1 It can be fluorine, chlorine, bromine, or iodine.
[0081] R 1 To R 6 Each of the following is independently hydrogen, cyano, substituted or unsubstituted C1 to C20 alkyl, substituted or unsubstituted C1 to C20 alkoxy, substituted or unsubstituted C2 to C20 alkenyl, substituted or unsubstituted C2 to C20 alkynyl, substituted or unsubstituted C3 to C20 cycloalkyl, substituted or unsubstituted C6 to C20 aryl, or substituted or unsubstituted C2 to C20 heteroaryl.
[0082] n is an integer that is either 0 or 1.
[0083] The compound represented by chemical formula 1 exhibits high high-temperature stability on the surface of the negative electrode, forming a solid electrolyte interface (SEI) with excellent ionic conductivity, and through -PO2X 1 The (especially -PO2F) functional group suppresses the side reactions of LiPF6 and reduces gas generation caused by electrolyte decomposition during high-temperature storage.
[0084] Specifically, the compound represented by Formula 1 can coordinate with the pyrolysis products of lithium salts such as LiPF6 or anions dissociated from lithium salts, thus forming a complex. The formation of this complex can stabilize the pyrolysis products of lithium salts such as LiPF6 or the anions dissociated from lithium salts. Therefore, it can suppress undesirable side reactions between anions and the electrolyte, prevent gas generation inside the rechargeable lithium battery, and thus significantly reduce the defect rate and improve the cycle life characteristics of the rechargeable lithium battery.
[0085] Compounds represented by chemical formula 1 are represented by chemical formula 1A or chemical formula 1B.
[0086]
[0087] In chemical formula 1A and chemical formula 1B,
[0088] X 1 It can be fluorine, chlorine, bromine, or iodine.
[0089] R 1 To R 6 Each is independently hydrogen, substituted or unsubstituted C1 to C10 alkyl, substituted or unsubstituted C1 to C10 alkoxy, substituted or unsubstituted C2 to C10 alkenyl, or substituted or unsubstituted C2 to C10 alkynyl.
[0090] In chemical formulas 1A and 1B, R3 and R 4 Each can be hydrogen, and R 1 R 2 R 5 and R 6 At least one of them may be a substituted or unsubstituted C1 to C10 alkyl, a substituted or unsubstituted C1 to C10 alkoxy, a substituted or unsubstituted C2 to C10 alkenyl, or a substituted or unsubstituted C2 to C10 alkynyl.
[0091] For example, a compound represented by chemical formula 1 can be represented by chemical formula 1A.
[0092] In a specific example, in chemical formula 1A, R 3 and R 4 Each can be hydrogen, and R 5 and R 6 At least one of them may be a substituted or unsubstituted C1 to C10 alkyl, a substituted or unsubstituted C1 to C10 alkoxy, a substituted or unsubstituted C2 to C10 alkenyl, or a substituted or unsubstituted C2 to C10 alkynyl.
[0093] For example, in chemical formula 1A, R 3 and R 4 Each can be hydrogen, and R 5 and R 6 At least one of them may be a substituted or unsubstituted C1 to C10 alkyl group.
[0094] Based on 100 parts by weight of total electrolyte, the content of the compound represented by chemical formula 1 may be greater than about 0.2 parts by weight and less than about 2.0 parts by weight, for example about 0.3 parts by weight to about 1.5 parts by weight, or about 0.5 parts by weight to about 1.5 parts by weight.
[0095] When the amount of the compound represented by chemical formula 1 is within the above range, a rechargeable lithium battery with improved high-temperature storage characteristics and cycle life characteristics can be realized.
[0096] For example, the compound represented by chemical formula 1 may be selected from the compounds of group 1, and may be, for example, 2-fluoro-1,3,2-dioxophosphanecyclopentane and 2-fluoro-4-methyl-1,3,2-dioxophosphanecyclopentane.
[0097] [Group 1]
[0098]
[0099] In addition to the aforementioned additives, additives may further include other additives.
[0100] Other additives may include at least one selected from vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, vinylethylene carbonate (VEC), adiponitrile (AN), succinate (SN), 1,3,6-hexanetricyanate (HTCN), propene sulpholol (PST), propane sulphololol (PS), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), and 2-fluorobiphenyl (2-FBP).
[0101] By further including the aforementioned other additives, cycle life can be further improved, or the gases generated from the positive and negative electrodes can be effectively controlled during high-temperature storage.
[0102] Based on the total weight of the electrolyte used in the rechargeable lithium battery, the content of other additives may be from about 0.2 parts by weight to 20 parts by weight, specifically from about 0.2 parts by weight to 15 parts by weight, for example from about 0.2 parts by weight to 10 parts by weight.
[0103] When the content of other additives is as described above, the increase in membrane resistance can be minimized, thereby contributing to the improvement of battery performance.
[0104] Non-aqueous organic solvents are used as media for transporting ions that participate in the electrochemical reactions of the battery.
[0105] Non-aqueous organic solvents can be carbonate solvents, ester solvents, ether solvents, ketone solvents, alcohol solvents, or proton-inert solvents.
[0106] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), and butyl carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, decanolactone, mevalonolactone, and caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran, etc. Additionally, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol and isopropanol, and proton-inert solvents may include nitriles (such as R-CN (where R is a hydrocarbon group having a C2 to C20 straight chain, branched chain or cyclic structure, and may include double bonds, aromatic rings or ether bonds), amides (such as dimethylformamide), dioxolane (such as 1,3-dioxolane), and sulfolane.
[0107] Non-aqueous organic solvents can be used alone or in mixtures, and when used in mixtures, the mixture ratio can be controlled according to the desired battery performance.
[0108] Carbonate solvents are prepared by mixing cyclic carbonates and linear carbonates. The performance of the electrolyte is improved when cyclic carbonates and linear carbonates are mixed together in a volume ratio of about 5:5 to about 1:9.
[0109] In particular, in embodiments, the non-aqueous organic solvent may include cyclic carbonates and linear carbonates in a volume ratio of about 5:5 to about 2:8, and as a specific example, cyclic carbonates and linear carbonates may be included in a volume ratio of about 4:6 to about 2:8.
[0110] As a more specific example, volume ratios of about 3:7 to about 2:8 may include cyclic carbonates and linear carbonates.
[0111] In addition to carbonate solvents, non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. In this paper, carbonate solvents and aromatic hydrocarbon organic solvents may be mixed in a volume ratio of about 1:1 to about 30:1.
[0112] Aromatic hydrocarbon organic solvents can be aromatic hydrocarbon compounds represented by chemical formula 3.
[0113] [Chemical Formula 3]
[0114]
[0115] In chemical formula 3, R 7 To R 12 They may be the same or different, and are selected from hydrogen, halogens, C1 to C10 alkyl, C1 to C10 haloalkyl and combinations thereof.
[0116] Specific examples of aromatic hydrocarbon organic solvents can be selected from benzene, fluorobenzene, 1,2-difluorobenzene, 1,3-difluorobenzene, 1,4-difluorobenzene, 1,2,3-trifluorobenzene, 1,2,4-trifluorobenzene, chlorobenzene, 1,2-dichlorobenzene, 1,3-dichlorobenzene, 1,4-dichlorobenzene, 1,2,3-trichlorobenzene, 1,2,4-trichlorobenzene, iodobenzene, 1,2-diiodobenzene, 1,3-diiodobenzene, 1,4-diiodobenzene, 1,2,3-triiodobenzene, 1,2,4-triiodobenzene, toluene, and fluoromethylbenzene. Benzene, 2,3-difluorotoluene, 2,4-difluorotoluene, 2,5-difluorotoluene, 2,3,4-trifluorotoluene, 2,3,5-trifluorotoluene, chlorotoluene, 2,3-dichlorotoluene, 2,4-dichlorotoluene, 2,5-dichlorotoluene, 2,3,4-trichlorotoluene, 2,3,5-trichlorotoluene, iodotoluene, 2,3-diiodotoluene, 2,4-diiodotoluene, 2,5-diiodotoluene, 2,3,4-triiodotoluene, 2,3,5-triiodotoluene, xylene and combinations thereof.
[0117] Lithium salts dissolved in non-aqueous organic solvents supply lithium ions in batteries, ensuring basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts include at least one supported salt selected from the following: LiPF6, LiBF4, lithium difluoro(oxalate)borate (LiDFOB), LiPO2F2, LiSbF6, LiAsF6, LiN(SO2C2F5)2, Li(CF3SO2)2N, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide, LiFSI), LiC4F9SO3, LiClO4, LiAlO2, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+1 SO2 (where x and y are natural numbers, for example, integers in the range of 1 to 20), LiCl, LiI, and LiB(C2O4)2 (lithium bis(oxalate)borate, LiBOB). Lithium salts can be used at concentrations ranging from about 0.1 M to about 2.0 M. When lithium salts are included in the above concentration range, the electrolyte can exhibit excellent performance and lithium-ion mobility due to optimal electrolyte conductivity and viscosity.
[0118] The positive electrode includes a positive electrode current collector and a positive electrode active material layer on the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material and carbon nanotubes.
[0119] Based on the total weight of the positive electrode active material layer, the content of carbon nanotubes can be greater than about 0.1 wt% and less than about 3.0 wt%, for example, greater than or equal to about 0.5 wt% and less than about 3.0 wt%, greater than or equal to about 0.5 wt% and less than or equal to about 2 wt%.
[0120] When the carbon nanotube content is within the above range, the amount of dispersant used to disperse the carbon nanotubes can be adjusted to an appropriate amount, and the increase in resistance caused by the increase in the amount of dispersant can be reduced, thereby preventing the deterioration of battery performance.
[0121] The average length of carbon nanotubes can be greater than or equal to about 5 μm and less than about 200 μm, for example about 5 μm to about 100 μm, for example about 10 μm to about 100 μm, or about 50 μm to about 100 μm.
[0122] When the average length of carbon nanotubes is within the above range, the coating uniformity of the positive electrode active material layer can be ensured, thereby increasing the immersion of the electrode plate in the electrolyte and reducing the electrode plate resistance.
[0123] The average length of a carbon nanotube refers to the average of the maximum distances between any two ends of a plurality of carbon nanotubes. The average length of the carbon nanotubes in this disclosure is the arithmetic mean of the lengths of a plurality of carbon-based nanostructures. The average length of the carbon nanotubes can be measured using a field radial scanning electron microscope. Furthermore, the carbon nanotubes according to embodiments of the present invention can be in the form of at least one of single-walled carbon nanotubes, double-walled carbon nanotubes, and multi-walled carbon nanotubes. Single-walled or double-walled carbon nanotubes can improve the dispersibility of slurries containing carbon nanotubes and exhibit excellent processability (e.g., coating) when forming an active material layer, while ensuring excellent conductivity of the active material layer formed using them.
[0124] Positive electrode active materials may include lithiated intercalation compounds that can reversibly insert and deintercalate lithium ions.
[0125] Specifically, a composite oxide containing nickel metal and lithium can be used.
[0126] Examples of positive electrode active materials may include compounds represented by any of the following chemical formulas.
[0127] Li a A 1-b X b D2(0.90≤a≤1.8, 0≤b≤0.5); Li a A 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a E 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a E2-b X b O 4-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);Li a Ni 1-b-c Co b X c D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α≤2);Li a Ni 1-b-c Co b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);Li a Ni 1-b-c Co b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);Li a Ni 1-b-c Mr b X c D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α≤2);Li a Ni 1-b-c Mr b X c O 2-α T α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);Li a Ni 1-b-c Mr b X c O 2-α T2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0<α<2);Li a Ni b HAVE BEEN c G d O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0.001≤d≤0.1);Li a Ni b Co c Mr d G e O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0.001≤e≤0.1);Lia NiG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn2G b O4(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4(0.90≤a≤1.8, 0≤g≤0.5); QO2; QS2; LiQS2; V2O5; LiV2O5; LiZO2; LiNiVO4; Li (3-f) J2(PO4)3 (0≤f≤2); Li (3-f) Fe2(PO4)3 (0≤f≤2); Li a FePO4 (0.90≤a≤1.8).
[0128] In the above chemical formulas, A is selected from Ni, Co, Mn and their combinations; X is selected from Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, rare earth elements and their combinations; D is selected from O, F, S, P and their combinations; E is selected from Co, Mn and their combinations; T is selected from F, S, P and their combinations; G is selected from Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V and their combinations; Q is selected from Ti, Mo, Mn and their combinations; Z is selected from Cr, V, Fe, Sc, Y and their combinations; and J is selected from V, Cr, Mn, Co, Ni, Cu and their combinations.
[0129] These compounds may form a coating on a surface or may be mixed with another compound having a coating. The coating may include at least one coating element compound selected from oxides, hydroxides, hydroxy oxides, oxycarbonates, and hydroxy carbonates of the coating element. The compound used for the coating may be amorphous or crystalline. Coating elements included in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or mixtures thereof. The coating process may include any conventional process, as long as it does not cause any adverse effects on the properties of the positive electrode active material (e.g., spraying, dipping), which is well known to those skilled in the art, and therefore its detailed description is omitted.
[0130] The positive active material may be, for example, at least one of the lithium composite oxides represented by Chemical Formula 2.
[0131] [Chemical Formula 2]
[0132] Li x M 1 1-y-z-w M 2 y M 3 z M 4 w (PO4) 1-t (O2) t
[0133] In Chemical Formula 2,
[0134] 0.5≤x<1.8, 0≤y≤1.0, 0≤z≤1.0, 0<y+z+w≤1.0, 0≤t≤1.0, 0≤w≤1.0, M 1 to M 3 are each independently any one selected from the group consisting of metals Ni, Co, Mn, Fe, Al, Sr, La, and combinations thereof, and M 4 is selected from Ti, Mg, Zr, Ca, Nb, P, F, B, and combinations thereof.
[0135] For example, the positive active material may be a lithium composite oxide represented by at least one of Chemical Formula 2-1 to Chemical Formula 2-4.
[0136] [Chemical Formula 2-1]
[0137] Li x1 Ni 1-y1-z1 Co y1 M 3 z1 M 4 w1 O2
[0138] In Chemical Formula 2-1,
[0139] M 3 is Mn, Al, or a combination thereof,
[0140] M 4 is Ti, Mg, Zr, Ca, Nb, P, F, B, or a combination thereof,
[0141] 0.9≤x1<1.2, 0≤y1≤0.2, 0<z1≤0.3, 0<y1+z1≤0.5, and 0≤w1≤0.1.
[0142] For example, the positive active material represented by Chemical Formula 2-1 may be LiNi 0.88 Co0.105 Al 0.015 O₂, LiNi 0.91 Co 0.075 Al 0.015 O₂, LiNi 0.94 Co 0.045 Al 0.015 O₂, LiNi 0.88 Co 0.105 Mn 0.015 O₂, LiNi 0.91 Co 0.075 Mn 0.015 O₂ or LiNi 0.94 Co 0.045 Mn 0.015 O₂.
[0143] [Chemical Formula 2-2]
[0144] Li x2 MnM 4 w2 O₂
[0145] In Chemical Formula 2-2,
[0146] 0.9≤x2<1.2, 0≤w2≤1.0, M 4 is selected from Ti, Mg, Zr, Ca, Nb, P, F, B or a combination thereof.
[0147] For example, the positive electrode active material represented by Chemical Formula 2-2 may be LiMnO₂.
[0148] [Chemical Formula 2-3]
[0149] Li x3 CoM 4 w3 O₂
[0150] In Chemical Formula 2-3,
[0151] M 4 is Ti, Mg, Zr, Ca, Nb, P, F, B or a combination thereof,
[0152] 0.5<x3≤1, and 0≤w3≤0.1.
[0153] For example, the positive electrode active material represented by Chemical Formula 2-3 may be LiCoO₂.
[0154] [Chemical Formula 2-4]
[0155] Li x4 Fe 1-z4 M 3 z4 M 4w4 PO4
[0156] In chemical formula 2-4,
[0157] M 3 It is Co, Ni or a combination thereof.
[0158] M 4 The elements are Ti, Mg, Zr, Ca, Nb, P, F, B, or combinations thereof.
[0159] 0.9≤x4≤1.8, 0≤z4≤0.3, and 0≤w4≤0.1.
[0160] For example, the positive electrode active material represented by chemical formula 2-4 can be LiFePO4.
[0161] Based on the total weight of the positive electrode active material layer, the content of the positive electrode active material can be from about 90 wt% to about 98 wt%.
[0162] In embodiments of the present invention, the positive electrode active material layer may include a binder. Based on the total weight of the positive electrode active material layer, the binder content may be from about 1 wt% to about 5 wt%.
[0163] The binder improves the bonding characteristics between the positive electrode active material particles and the bonding characteristics between the positive electrode active material particles and the positive electrode current collector. Examples of binders include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic styrene-butadiene rubber, epoxy resin, and nylon, but are not limited to these.
[0164] Al can be used as a positive electrode current collector, but is not limited to this.
[0165] The negative electrode includes a negative electrode current collector and a negative electrode active material layer, the negative electrode active material layer including negative electrode active material formed on the negative electrode current collector.
[0166] The negative electrode active material may include materials that can reversibly insert / deintercalate lithium ions, lithium metal, lithium metal alloys, materials that can be doped / dedoped with lithium, or transition metal oxides.
[0167] Materials that can reversibly insert / deintercalate lithium ions can be carbon materials. These carbon materials can be any commonly used carbon-based negative electrode active material in rechargeable lithium batteries. Examples of carbon materials can be crystalline carbon, amorphous carbon, or combinations thereof. Examples of crystalline carbon include graphite, such as amorphous, flake, scaly, spherical, or fibrous natural or artificial graphite. Examples of amorphous carbon include soft carbon, hard carbon, mesophase pitch carbonization products, or calcined coke.
[0168] The lithium metal alloy may be an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn.
[0169] The material capable of doping / dedoping lithium may be Si, a Si-C composite material, SiO x (0<x<2), a Si-Q alloy (where Q is an element selected from an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element other than Si, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof), Sn, SnO₂, Sn-R (where R is an element selected from an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element other than Sn, a Group 15 element, a Group 16 element, a transition metal, a rare earth element, and combinations thereof), and at least one thereof may be mixed with SiO₂. Elements Q and R may be selected from Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn (R does not include Sn), In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof.
[0170] The transition metal oxide may include vanadium oxide, vanadium oxide, or lithium titanium oxide.
[0171] The negative active material according to the embodiment may be graphite, or may include a Si composite material together with graphite.
[0172] When the negative active material includes the Si composite material and graphite together, the Si composite material and graphite may be included in the form of a mixture, and the Si composite material and graphite may be included in a weight ratio of about 1:99 to about 50:50. More specifically, the Si composite material and graphite may be included in a weight ratio of about 3:97 to about 20:80.
[0173] The Si composite material includes a core containing Si-based particles and an amorphous carbon coating. For example, the Si-based particles may include at least one of Si particles, a Si-C composite material, SiO x (0<x≤2) and a Si alloy. For example, the Si-C composite material may include Si particles and crystalline carbon, and an amorphous carbon coating is coated on the surface of the Si-C composite material.
[0174] The Si-based particles may have an average particle diameter of about 50 nm to about 200 nm.
[0175] When the average particle size of Si particles is within the above range, volume expansion during charging and discharging can be suppressed, and interruption of the conductive path due to particle breakage during charging and discharging can be prevented.
[0176] Based on the total weight of the negative electrode active material, the content of Si particles can be from about 1 wt% to about 60 wt%, for example, from about 3 wt% to about 60 wt%.
[0177] According to another embodiment, the negative electrode active material may further include crystalline carbon and the aforementioned Si-C composite material together.
[0178] When the negative electrode active material includes Si-C composite material and crystalline carbon together, the Si-C composite material and crystalline carbon can be included in the form of a mixture, and in this case, the Si-C composite material and crystalline carbon can be included in a weight ratio of about 1:99 to about 50:50. More specifically, the Si-C composite material and crystalline carbon can be included in a weight ratio of about 5:95 to about 20:80.
[0179] Crystalline carbon may include, for example, graphite, and more specifically, natural graphite, artificial graphite, or mixtures thereof.
[0180] The average particle size of crystalline carbon can be from about 5 μm to about 30 μm.
[0181] In this specification, the average particle size (D50) can be the particle size representing 50% of the volume in the cumulative size-distribution curve.
[0182] The Si-C composite material may further include a shell surrounding the surface of the Si-C composite material, and the shell may include amorphous carbon.
[0183] Amorphous carbon may include soft carbon, hard carbon, products of mesophase pitch carbonization, calcined coke, or mixtures thereof.
[0184] Based on 100 parts by weight of carbon-based active material, the content of amorphous carbon can be from about 1 part by weight to about 50 parts by weight, for example, from about 5 parts by weight to about 50 parts by weight, or from about 10 parts by weight to about 50 parts by weight.
[0185] Amorphous carbon precursors may include coal pitch, mesophase pitch, petroleum pitch, coal oil, petroleum heavy oil, or polymer resins such as phenolic resin, furan resin, or polyimide resin.
[0186] In the negative electrode active material layer, the content of the negative electrode active material can be from about 95 wt% to about 99 wt%, based on the total weight of the negative electrode active material layer.
[0187] In embodiments of this disclosure, the negative electrode active material layer includes a binder and optionally a conductive material. In the negative electrode active material layer, the binder content may be from about 1 wt% to about 5 wt% based on the total weight of the negative electrode active material layer. When the negative electrode active material layer includes a conductive material, the negative electrode active material layer comprises about 90 wt% to about 98 wt% of negative electrode active material, about 1 wt% to about 5 wt% of binder, and about 1 wt% to about 5 wt% of conductive material.
[0188] Binders improve the bonding properties between the negative electrode active material particles and between them and the negative electrode current collector. Binders include non-water-soluble binders, water-soluble binders, or combinations thereof.
[0189] The non-water-soluble adhesive may be selected from polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.
[0190] Water-soluble adhesives can be rubber-based adhesives or polymer resin adhesives. Rubber-based adhesives can be selected from styrene-butadiene rubber, acrylic styrene-butadiene rubber (SBR), acrylonitrile-butadiene rubber, acrylic rubber, butyl rubber, fluororubber, and combinations thereof. Polymer resin adhesives can be selected from polytetrafluoroethylene, ethylene-propylene copolymer, polyethylene oxide, polyvinylpyrrolidone, polyepoxychloropropane, polyphosphazene, polyacrylonitrile, polystyrene, ethylene-propylene-diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, and combinations thereof.
[0191] When a water-soluble binder is used as a negative electrode binder, a cellulose compound can further be used as a thickener to provide viscosity. Cellulose compounds include one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts. The alkali metal can be Na, K, or Li. Based on 100 parts by weight of the negative electrode active material, the content of this thickener can be from about 0.1 parts by weight to about 3 parts by weight.
[0192] This includes conductive materials to provide electrode conductivity, and any conductive material can be used as a conductive material unless it causes a chemical change. Examples of conductive materials include carbon-based materials such as natural graphite, synthetic graphite, carbon black, acetylene black, Ketjen black, and carbon fibers; metallic materials including metal powders or fibers of copper, nickel, aluminum, and silver; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0193] The negative electrode current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, polymer substrate coated with conductive metal, and combinations thereof.
[0194] Depending on the type of rechargeable lithium battery, a separator may be present between the negative electrode and the positive electrode. Such a separator may include polyethylene separators, polypropylene separators, polyvinylidene fluoride separators, or multiple layers thereof, such as polyethylene / polypropylene double-layer separators, polyethylene / polypropylene / polypropylene triple-layer separators, and polypropylene / polypropylene / polypropylene triple-layer separators.
[0195] Embodiments and comparative examples of the present invention are described below. However, these embodiments are in no way intended to limit the scope of the invention.
[0196] Manufacturing of rechargeable lithium battery cells
[0197] Example 1
[0198] LiNi will be used as the positive electrode active material 0.88 Co 0.105 Al 0.015 O2, polyvinylidene fluoride as a binder, and carbon nanotubes (average length: 50 μm) as a conductive material are mixed in a weight ratio of 96:3:1 and dispersed in N-methylpyrrolidone to prepare a positive electrode active material slurry.
[0199] The positive electrode active material slurry was coated onto a 15 μm thick Al foil, dried at 100 °C, and then extruded to prepare the positive electrode.
[0200] As the negative electrode active material, a mixture of artificial graphite and Si composite material with a weight ratio of 93:7 was used, and the negative electrode active material, styrene-butadiene rubber binder and carboxymethyl cellulose were mixed with a weight ratio of 98:1:1 and dispersed in distilled water to prepare a negative electrode active material slurry.
[0201] The Si composite material comprises a core containing artificial graphite and silicon particles, with coal tar pitch coated on the surface of the core.
[0202] The negative electrode active material slurry was coated onto a 10 μm thick Cu foil, dried at 100 °C, and then extruded to prepare the negative electrode.
[0203] The electrode assembly is prepared by assembling the prepared positive and negative electrodes and a polyethylene separator with a thickness of 25 μm, and then injecting electrolyte to prepare a rechargeable lithium battery cell.
[0204] The electrolyte composition is as follows.
[0205] (Composition of the electrolyte)
[0206] Lithium salt: 1.5M LiPF6
[0207] Non-aqueous organic solvent: ethylene carbonate: ethyl methyl carbonate: dimethyl carbonate (EC:EMC:DMC = 20:10:70 volume ratio)
[0208] Additives: 0.75 parts by weight of 2-fluoro-4-methyl-1,3,2-dioxophosphazenecyclopentane, 10 parts by weight of fluoroethylene carbonate (FEC), and 0.5 parts by weight of succinate (SN).
[0209] (In this article, in the composition of the electrolyte, "parts by weight" means the relative content of the additives to 100 parts by weight of all electrolyte (lithium salt + non-aqueous organic solvent excluding the additives).)
[0210] Comparative Example 1
[0211] The rechargeable lithium battery cell was manufactured in essentially the same manner as in Example 1, except that an electrolyte without additives (2-fluoro-4-methyl-1,3,2-dioxophosphazenecyclopentane) was used.
[0212] Examples 2 and 3
[0213] The rechargeable lithium battery cell was manufactured in essentially the same manner as in Example 1, except that the respective contents of carbon nanotubes were changed to 0.5 wt% and 2.0 wt% to manufacture the positive electrode.
[0214] Compare Examples 2 and 3
[0215] The rechargeable lithium battery cell was manufactured in essentially the same manner as in Example 1, except that the respective contents of carbon nanotubes were changed to 0.1 wt% and 3.0 wt% to manufacture the positive electrode.
[0216] Examples 4 and 5
[0217] The rechargeable lithium battery cell was manufactured in essentially the same manner as in Example 1, except that the respective contents of the additives (2-fluoro-4-methyl-1,3,2-dioxophosphazenecyclopentane) were changed to 0.5 parts by weight and 1.5 parts by weight, respectively, to manufacture the electrolyte.
[0218] Compare Examples 4 and 5
[0219] The rechargeable lithium battery cell was manufactured in essentially the same manner as in Example 1, except that the respective contents of the additives (2-fluoro-4-methyl-1,3,2-dioxophosphazenecyclopentane) were changed to 0.2 parts by weight and 2.0 parts by weight, respectively, to manufacture the electrolyte.
[0220] Examples 6 and 7
[0221] The rechargeable lithium battery cell was manufactured in essentially the same manner as in Example 1, except that the average lengths of the carbon nanotubes were changed to 5 μm and 100 μm, respectively, to manufacture the positive electrode.
[0222] Compare Examples 6 and 7
[0223] The rechargeable lithium battery cell was manufactured in essentially the same manner as in Example 1, except that the average lengths of the carbon nanotubes were changed to 1 μm and 200 μm, respectively, to manufacture the positive electrode.
[0224] The following components shown in Table 1 are used to manufacture rechargeable lithium battery cells.
[0225] (Table 1)
[0226]
[0227] Assessment 1: Electrolyte Impregnation Assessment
[0228] Electrode assemblies according to Examples 1 to 7 and Comparative Examples 1 to 7 are immersed in electrolyte by injecting electrolyte into them.
[0229] An electrolyte was prepared by using a mixed solvent of EC / EMC / DMC (volume ratio of 20 / 10 / 70) to prepare a 1.5 M LiPF6 solution and adding 0 to 3 parts by weight of 2-fluoro-4-methyl-1,3,2-dioxophosphazenecyclopentane.
[0230] Calculate the amount of electrolyte immersed in the electrode assembly per hour (immersion amount) according to Equation 1.
[0231] [Equation 1]
[0232] Impregnation amount = (Weight of the electrode assembly after impregnation in the electrolyte) - (Initial weight of the electrode assembly)
[0233] The results are shown in Table 2.
[0234] Evaluation 2: Evaluation of the increase rate of DC resistance after high-temperature storage
[0235] The initial DC resistance (DCIR) of the rechargeable lithium battery cells according to Examples 1 to 7 and Comparative Examples 1 to 7 was measured as ΔV / ΔI (voltage change / current change). After setting the maximum energy state inside the battery cell to a fully charged state (SOC 100%), the battery cell was stored at a high temperature (60°C) for 30 days, and then the DC resistance was measured again to calculate the DCIR increase rate (%) according to Equation 2. The results are shown in Table 2.
[0236] [Equation 2]
[0237] DCIR increase rate = (DCIR after 30 days / Initial DCIR) × 100%
[0238] Evaluation 3: Evaluation of High-Temperature Cycling Life Characteristics
[0239] The rechargeable lithium battery cells according to Examples 1 to 7 and Comparative Examples 1 to 7 were charged and discharged once at 0.2C, and then the charge and discharge capacity (before storage at high temperature) was measured.
[0240] In addition, the rechargeable lithium battery cells according to Examples 1 to 7 and Comparative Examples 1 to 7 were charged to 100% SOC (charged to 100% of the total charge capacity of the battery cell when the total charge capacity of the battery cell was 100%), then stored at 60°C for 5 hours, and initially charged and discharged at 0.5C. In this paper, the charge and discharge characteristics of the battery cells were evaluated by measuring the charge and discharge capacity and calculating the discharge capacity ratio of the 300th discharge capacity to the first discharge capacity, and the retention rate (%) results are shown in Table 2.
[0241] (Table 2)
[0242]
[0243] Referring to Table 2, the rechargeable lithium battery cell according to the embodiment has a larger amount of impregnating electrolyte than the battery cell according to the comparative example, thus exhibiting improved high-temperature cycle life characteristics and resistance characteristics after high-temperature storage.
[0244] Accordingly, the rechargeable lithium battery cell according to an exemplary embodiment of the present invention exhibits improved immersion characteristics in the electrolyte, thus achieving excellent cycle characteristics. Furthermore, it exhibits reduced resistance after high-temperature storage, thus demonstrating improved high-temperature stability.
[0245] Although the invention has been described in conjunction with exemplary embodiments now regarded as practice, it should be understood that the invention is not limited to the disclosed embodiments. Rather, the invention is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A rechargeable lithium battery, comprising: The positive electrode includes the positive electrode active material layer; The negative electrode includes the negative electrode active material layer; and Electrolytes including non-aqueous organic solvents, lithium salts, and additives. The positive electrode active material layer includes a positive electrode active material and carbon nanotubes, and Based on the total weight of the positive electrode active material layer, the content of the carbon nanotubes is greater than 0.1 wt% and less than 3.0 wt%, and The additives include compounds represented by chemical formula 1: [Chemical Formula 1] In chemical formula 1, X 1 It can be fluorine, chlorine, bromine, or iodine. R 1 To R 6 Each of the following is independently hydrogen, cyano, substituted or unsubstituted C1 to C20 alkyl, substituted or unsubstituted C1 to C20 alkoxy, substituted or unsubstituted C2 to C20 alkenyl, substituted or unsubstituted C2 to C20 alkynyl, substituted or unsubstituted C3 to C20 cycloalkyl, substituted or unsubstituted C6 to C20 aryl, or substituted or unsubstituted C2 to C20 heteroaryl. "Substitution" refers to the substitution of hydrogen atoms in a compound by a substituent selected from the following: halogen atom, hydroxyl, nitro, cyano, amino, azide, amidine, hydrazine, hydrazone, carbonyl, carbamoyl, thiol, ester, carboxyl or a salt thereof, sulfonic acid or a salt thereof, phosphate or a salt thereof, C1 to C20 alkyl, C2 to C20 alkenyl, C2 to C20 alkynyl, C6 to C30 aryl, C7 to C30 aralkyl, C1 to C4 alkoxy, C1 to C20 heteroalkyl, C3 to C20 heteroaralkyl, C3 to C30 cycloalkyl, C3 to C15 cycloalkenyl, C6 to C15 cycloalkynyl, C2 to C20 heterocycloalkyl, and combinations thereof, wherein the halogen atom is F, Br, Cl, or I, and n is an integer that is either 0 or 1. Based on 100 parts by weight of total electrolyte, the content of the compound represented by chemical formula 1 is greater than 0.2 parts by weight and less than 2.0 parts by weight. The average length of the carbon nanotubes is greater than or equal to 5 μm and less than 200 μm.
2. The rechargeable lithium battery as described in claim 1, wherein, The compounds represented by Chemical Formula 1 include compounds represented by Chemical Formula 1A or Chemical Formula 1B: [Chemical Formula 1A] [Chemical Formula 1B] Among them, in chemical formula 1A and chemical formula 1B, X 1 It can be fluorine-, chloro-, bromine-, or iodine-based, and R 1 To R 6 Each is independently hydrogen, substituted or unsubstituted C1 to C10 alkyl, substituted or unsubstituted C1 to C10 alkoxy, substituted or unsubstituted C2 to C10 alkenyl, or substituted or unsubstituted C2 to C10 alkynyl.
3. The rechargeable lithium battery as described in claim 2, wherein, In chemical formulas 1A and 1B, R 3 and R 4 Each is hydrogen, and R 1 R 2 R 5 and R 6 At least one of them is a substituted or unsubstituted C1 to C10 alkyl, a substituted or unsubstituted C1 to C10 alkoxy, a substituted or unsubstituted C2 to C10 alkenyl, or a substituted or unsubstituted C2 to C10 alkynyl.
4. The rechargeable lithium battery as described in claim 2, wherein, The compound represented by chemical formula 1 is selected from at least one of the compounds in group 1: [Group 1] 。 5. The rechargeable lithium battery as described in claim 1, wherein, The additive further includes at least one other additive selected from vinylene carbonate, fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, cyanoethylene carbonate, vinylethylene carbonate, adiponitrile, succinate, 1,3,6-hexanetricyanate, propene sulphol, propane sulphol, lithium tetrafluoroborate, lithium difluorophosphate, and 2-fluorobiphenyl.
6. The rechargeable lithium battery as described in claim 1, wherein, The average length of the carbon nanotubes is between 5 μm and 100 μm.
7. The rechargeable lithium battery as described in claim 1, wherein, The positive electrode active material is at least one type of lithium composite oxide represented by chemical formula 2: [Chemical Formula 2] Li x M 1 1-y-z-w M 2 y M 3 z M 4 w (PO4) 1-t (O2) t In chemical formula 2, M 1 To M 3 Each is independently selected from any one of the metals chosen from Ni, Co, Mn, Fe, Al, Sr, La, and combinations thereof. M 4 The elements are Ti, Mg, Zr, Ca, Nb, P, F, B, or combinations thereof. 0.5≤x<1.8, 0≤y≤1.0, 0≤z≤1.0, 0<y+z+w≤1.0, 0≤t≤1.0, and 0≤w≤1.
0.
8. The rechargeable lithium battery according to claim 7, wherein the positive active material is a lithium composite oxide represented by at least one of Chemical Formula 2-1 to Chemical Formula 2-4: [Chemical Formula 2-1] Li x1 Ni 1-y1-z1 Co y1 M 3 z1 M 4 w1 O2 wherein, in Chemical Formula 2-1, M 3 Mn, Al, or a combination thereof M 4 The elements are Ti, Mg, Zr, Ca, Nb, P, F, B, or combinations thereof. 0.9≤x1<1.2, 0≤y1≤0.2, 0<z1≤0.3, 0<y1+z1≤0.5, and 0≤w1≤0.1, [Chemical Formula 2-2] The x2 MnM 4 w2 O2 wherein, in Chemical Formula 2-2, 0.9 ≤ x² < 1.2, 0 ≤ w² ≤ 1.0, and M 4 Selected from Ti, Mg, Zr, Ca, Nb, P, F, B, or combinations thereof, [Chemical Formula 2-3] I read x3 With 4 w3 O2 wherein, in Chemical Formula 2-3, M 4 The elements are Ti, Mg, Zr, Ca, Nb, P, F, B, or combinations thereof. 0.5<x3≤1, and 0≤w3≤0.1, [Chemical Formula 2-4] Li x4 Fe 1-z4 M 3 z4 M 4 w4 PO4 wherein, in Chemical Formula 2-4, M 3 It is Co, Ni or a combination thereof. M 4 The elements are Ti, Mg, Zr, Ca, Nb, P, F, B, or combinations thereof. 0.9≤x4≤1.8, 0≤z4≤0.3, and 0≤w4≤0.1.
Citation Information
Patent Citations
Method and device for positioning
KR1020210113345A
Electrolyte for lithium secondary battery and lithium secondary battery including same
CN111293361A
Lithium battery electrolyte additive and preparation method and application thereof
CN113130996A
